Using multimedia hints to facilitate conceptual problem solving in physics: investigating the effects of multiple modalities - Wu, Xian; Li, Yaoguang; Zu, Tianlong; Hutson, John; Loschky, Lester C.; Rebello, N. Sanjay (Frontiers in Education, 2025)
Multimedia hints are widely used in educational materials to support conceptual learning, yet their comparative effectiveness across modalities remains underexplored. Prior studies suggest that graphical hints can enhance learners’ performance on physics problems, but it is unclear how they interact with other modalities such as text and voice. Understanding these interactions is essential for designing effective instructional tools. In this study, we investigated the effects of graphical, typographic, and vocal hints, individually and in combination, on students’ problem-solving performance. A total of 162 students from a conceptual physics course participated in individual interviews and solved four sets of isomorphic problems. Each set included an initial problem (pretest), six training problems, a near transfer problem, and a far transfer problem. We employed a 2 × 2 × 2 between-subject quasi-experimental design to examine the effects of the three hint modalities. Results from paired-sample t-tests showed significant performance gains from pretest to both near and far transfer tasks, indicating that solving isomorphic problems with hints promotes learning. Among modalities, graphical hints led to better training performance than typographic or vocal hints. Notably, combining typographic and vocal hints produced worse outcomes than using either modality alone, contradicting the auditory superiority effect and suggesting potential cognitive overload. These findings highlight the effectiveness of visual support and caution against indiscriminate integration of multiple hint modalities. We provide evidence-based recommendations for designing multimedia instructional materials that optimize cognitive processing and support conceptual problem solving in physics.